Effectiveness Blended Learning During Pandemic in Indonesia: A Meta-Analysis - Watrianthos, Ronal; Hasibuan, Rosmidah; Rimbano, Dheo; Jalinus, Nizwardi; Abdullah, Rijal (Jurnal Pendidikan MIPA, 2021)
The current blended learning method, which mixes online and traditional classroom instruction, is appropriate for the epidemic. According to various research studies, blended learning benefits students by allowing them to study independently without regard for location or time constraints. This article explores and describes the use of the blended learning paradigm during a pandemic using a meta-analysis technique. The objective is to determine the effect of blended learning on learning outcomes; according to the conclusions of a research released in 2021 based on ten published articles, employing the blended learning approach greatly improved learning outcomes during the pandemic, with an effect size value of 1.21. However, the outcomes of this study suggest that publication bias exists as a result of an unbalanced distribution of effect sizes.Keywords: blended learning, pandemic, meta-analysis DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp270-278